Access to Head Start and Maternal Labor Supply: Experimental and Quasi-Experimental Evidence - Jocelyn Wikle; Riley Wilson (Institute of Labor Economics (IZA), 2021)
We explore how access to Head Start impacts maternal labor supply. By relaxing child care constraints, public preschool options like Head Start might lead mothers to reallocate time between employment, child care, and other activities. Using the 1990s enrollment and funding expansions and the 2002 Head Start Impact Study randomized control trial, we show that Head Start increases short-run employment and wage earnings of single mothers. The increase in labor supply does not appear to reduce quality parent-child interactions. Viewing Head Start as a bundle of family-level treatments can shed new light on the impacts of the program beyond children.
Keywords: J13; J22; H4; I28; H52; I38; 330; Head Start; child care subsidies; maternal labor supply